Systemic inflammatory diseases in Internal Medicine at the CNHU-HKM of Cotonou: frequency, clinical, and immunological aspects. - WANVOEGBE, FINANGNON ARMAND; AGBODANDE, KOUESSI ANTHELME; AZON ÉPSE KOUANOU, ANGÈLE (My University, 2022)
Introduction: Systemic inflammatory diseases (autoimmune and autoinflammatory) are quite infrequent and challenging to diagnose. The intent of this study is to determine the hospital frequency, clinical, and immunological aspects of these diseases in the internal medicine department of the CNHU-HKM of Cotonou. Methods: This was a cross-sectional, descriptive study that was conducted from March 30 to October 30, 2018, and involved patients followed in the Internal Medicine Department of the CNHU-HKM for systemic inflammatory diseases Results: During the study period (7 months), 699 patients had consulted the service. We counted 23 patients for our study, i.e. a frequency of 3.3%. The average age was 44 (±12) years with extremes of 24 to 64 years. The majority of our patients were women with a sex ratio (M/F) of 0.09. Prolonged fever was the primary reason for admission (34.8%), followed by polyarthralgia (25%). Systemic lupus was the most represented (52.2%), followed by scleroderma (13%), mixed connectivity (13%). As for the class of systemic inflammatory diseases, systemic autoimmune diseases were the most represented (87.0%). Anti-nuclear antibodies were the most frequent (56.5%). Conclusion: Systemic inflammatory diseases are little known in Benin Republic. In fact, their clinical and immunological presentations are quite polymorphic.
Keywords: Antibodies; Cotonou; Auto-inflammatory; Autoimmune.